2014
DOI: 10.1186/1471-2369-15-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microcirculatory impairment by transcutaneous oxymetry monitoring during hemodialysis: an observational study

Abstract: BackgroundLittle is known about the effects of intermittent hemodialysis on microcirculatory perfusion. The aim of this study is to assess the effects of hemodialysis on microvascular perfusion using transcutaneous oxymetry (TCPO2).MethodsIn this observational study, hourly TCPO2 measurements were performed during hemodialysis sessions. Ankle brachial index (ABI) was carried out to classify patients according their vascular condition.Results50 patients (mean age 70 ± 8 years old) were enrolled. Mean TCPO2 decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…have observed severe ischemia (defined as a transcutaneous (TcpO 2 ) levels <30 mmHg, and critical ischemia (TcpO 2 <10 mmHg) during HD in 47% and 16% of patients, respectively (81). Critical ischemia was only observed in those patients with peripheral vascular disease, showing the importance of the deleterious interaction between preexisting abnormalities in the vascular tree and the effect of HD.…”
Section: Systemic Consequences Of Hypoxia At Tissue Levelmentioning
confidence: 99%
“…have observed severe ischemia (defined as a transcutaneous (TcpO 2 ) levels <30 mmHg, and critical ischemia (TcpO 2 <10 mmHg) during HD in 47% and 16% of patients, respectively (81). Critical ischemia was only observed in those patients with peripheral vascular disease, showing the importance of the deleterious interaction between preexisting abnormalities in the vascular tree and the effect of HD.…”
Section: Systemic Consequences Of Hypoxia At Tissue Levelmentioning
confidence: 99%
“…Overall, TcpO 2 declined from 45.7 ± 15.5 vs. 33.5 ± 15.6 mm Hg. This tissue again shows that significant changes in tissue perfusion may accompany routine HD treatments [40]. …”
Section: Changes In Perfusion Are Important But How Can They Be Measmentioning
confidence: 99%
“…Other investigations have shown that tissue perfusion can be affected by HD, and subclinical perfusion disturbances due to hemodialysis have been reported throughout the entire body 24 , 54 , 55 . HD has been shown to induce cardiac stunning in patients due to the maldistribution of myocardial blood flow, which ultimately cause irreversible structural change of the myocardium 25 .…”
Section: Discussionmentioning
confidence: 99%